Does Insurance Status Affect Treatment of Children With Tibial Spine Fractures?. Issue 14 (December 2021) - Smith, Haley E.; Mistovich, R. Justin; Cruz, Aristides I.; Leska, Tomasina M.; Ganley, Theodore J.; Aoyama, Julien T.; Ellis, Henry B.; Fabricant, Peter D.; Green, Daniel W.; Jagodzinski, Jason; Johnson, Benjamin; et al.
Background: Previous studies have reported disparities in orthopaedic care resulting from demographic factors, including insurance status. However, the effect of insurance on pediatric tibial spine fractures (TSFs), an uncommon but significant injury, is unknown. Purpose: To assess the effect of insurance status on the evaluation and treatment of TSFs in children and adolescents. Study Design: Cross-sectional study; Level of evidence, 3. Methods: We performed a retrospective cohort study of TSFs treated at 10 institutions between 2000 and 2019. Demographic data were collected, as was information regarding pre-, intra-, and postoperative treatment, with attention to delays in management and differences in care. Surgical and nonsurgical fractures were included, but a separate analysis of surgical patients was performed. Univariate analysis was followed by purposeful entry multivariate regression to adjust for confounding factors. Results: Data were collected on 434 patients (mean ± SD age, 11.7 ± 3.0 years) of which 61.1% had private (commercial) insurance. Magnetic resonance imaging (MRI) was obtained at similar rates for children with public and private insurance (41.4% vs 41.9%, respectively; P ≥ .999). However, multivariate analysis revealed that those with MRI performed ≥21 days after injury were 5.3 times more likely to have public insurance (95% CI, 1.3-21.7; P = .02). Of the 434 patients included, 365 required surgery. Similar to the overall cohort, those in the surgical subgroup with MRI ≥21 days from injury were 4.8 times more likely to have public insurance (95% CI, 1.2-19.6; P = .03). Children who underwent surgery ≥21 days after injury were 2.5 times more likely to have public insurance (95% CI, 1.1-6.1; P = .04). However, there were no differences in the nature of the surgery or findings at surgery. Those who were publicly insured were 4.1 times more likely to be immobilized in a cast rather than a brace postoperatively (95% CI, 2.3-7.4; P < .001). Conclusion: Children with public insurance and a TSF were more likely to experience delays with MRI and surgical treatment than those with private insurance. However, there were no differences in the nature of the surgery or findings at surgery. Additionally, patients with public insurance were more likely to undergo postoperative casting rather than bracing.